Valuing Biodiversity for Use in Pharmaceutical Research - Simpson, R. David; Sedjo, Roger A.; Reid, John W. (Journal of Political Economy, 1996)
"Biodiversity prospecting" has been touted as a mechanism for both discovering new pharmaceutical products and saving endangered ecosystems. It is unclear what values may arise from such activities, however. Evidence from transactions is incomplete and existing theoretical models are flawed. We calculate an upper bound on the value of the "marginal species." Even under favorable assumptions this bound is modest. Slightly modified assumptions lead to drastically lower estimates. We extend our findings to the value of the marginal hectare of habitat and find that the incentives for habitat conservation generated by private pharmaceutical research are also, at best, very modest.